From Endothelial Dysfunction to Arterial Stiffness in Diabetes Mellitus - Giraldo-Grueso, Manuel; Echeverri, Darío (Current Diabetes Reviews, 2020)
Prevalence of diabetes mellitus has increased drastically over time, especially in more populous countries such as the United States, India, and China. Patients with diabetes have an increased risk of major cardiovascular events such as acute myocardial infarction, cerebrovascular disease, and peripheral vascular disease. Arterial stiffness is a process related to aging and vascular, metabolic, cellular and physiological deterioration. In recent years, it has been described as an independent predictor of cardiovascular mortality and coronary artery disease. Additionally, it plays an important role in the measurement of chronic disease progression. Recent studies have suggested a strong relationship between diabetes mellitus and arterial stiffness since they share a similar pathophysiology involving endothelial dysfunction. The literature has shown that microvascular and macrovascular complications in diabetic patients could be screened and measured with arterial stiffness. Additionally, new evidence proposes that there is a relationship between blood glucose levels, microalbuminuria, and arterial stiffness. Moreover, arterial stiffness predicts cardiovascular risk and is independently associated with mortality in diabetic patients. Abnormal arterial stiffness values in diabetic patients should alert the clinician to the presence of vascular disease, which merits early study and treatment. We await more studies to determine if arterial stiffness could be considered a routine useful non-invasive tool in the evaluation of diabetic patients. There is enough evidence to conclude that arterial stiffness is related to the progression of diabetes mellitus.
Keywords: vascular stiffness